Emotional Intelligence Factors Affecting the Active Learning Management of Early Childhood Teachers in Pathum Thani Province - Pantuworakul, Kullachat; Nuansri, Mesa (Ratchaphruek Journal, 2026)
This research aimed to: (1) study the emotional intelligence of early childhood teachers, (2) investigate their implementation of active learning, and (3) explore the emotional intelligence factors that influence active learning management among early childhood teachers in Pathum Thani Province. The sample consisted of 300 teachers under the Pathum Thani Primary Educational Service Area Office, selected through multi-stage random sampling. The research instrument was a five-point Likert scale questionnaire, with reliability coefficients of 0.95 for the emotional intelligence scale and 0.96 for the active learning management scale. Data were analysed using percentages, means, standard deviations, and stepwise multiple regression. The research findings revealed that: (1) the overall emotional intelligence of early childhood teachers was at a high level ( = 3.82, S.D. = 0.60); (2) the overall level of active learning management was also high ( = 3.92, S.D. = 0.53); and (3) emotional intelligence factors significantly influencing active learning management were self-awareness, social skills, and empathy, which together accounted for 88.10% of the predictive variance.